Pengembangan Modul Pelaporan Keuangan Berbasis SAK EMKM sebagai Media Komunikasi Bisnis pada UMKM di Tasikmalaya - Gypari, Ilham Nouval; Juliansyah, Ardiwa; Puteri, Nazwa Herwiandiny; Hawa, Dinda Siti; Nababan, Pebrianisa; Renata, Renata (Welfare : Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to develop a simple financial reporting module based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) as a business communication tool for MSMEs in Tasikmalaya City, particularly Bakmie Tjap Laku and Warkop Polar. The method used is Participatory Action Research (PAR), which emphasizes the active involvement of business owners in every stage, including problem identification, needs analysis, module development, implementation, and continuous evaluation. Data were collected through observation, interviews, and documentation of the financial recording practices of the MSMEs. The results of the program indicate that financial recording practices are still simple and have not yet followed the structure required by SAK EMKM. Through a participatory approach, the developed module was able to improve the understanding and skills of MSME owners in recording transactions and preparing financial statements.